Expression of the fission yeast cell cycle regulator cdc25 induces de novo shoot formation in tobacco: evidence of a cytokinin-like effect by this mitotic activator - Suchomelová, Petra; Velgová, Denisa; Masek, Tomás; Francis, Dennis; Rogers, Hilary J; Marchbank, Angela M; Lipavská, Helena (Plant physiology and biochemistry, 2004)
During the last decade, the cell cycle and its control by cyclin-dependent kinases (CDKs) has been extensively studied in eukaryotes. The regulation of CDK activity includes, among others, its activation by Cdc25 phosphatase at G2/M. However, within the plant kingdom studies of this regulation have lagged behind and a plant cdc25 homologue has not been identified yet. Here, we report on the effects of transformation of tobacco (Nicotiana tabacum L., cv. Samsun) with fission yeast (Schizosaccharomyces pombe) cdc25 (Spcdc25) on de novo plant organ formation, a process dependent on rate and orientation of cell division. On shoot-inducing medium (low 1-naphthylacetic acid (NAA), high 6-benzylaminopurine (BAP)) the number of shoots formed on internode segments cultured from transgenic plants was substantially higher than in the non-transformed controls. Anatomical observations indicated that the shoot formation process was accelerated but with no changes in the quality and sequence of shoot development. Surprisingly, and in contrast to the controls, when on root-inducing medium (high NAA, low BAP) cultured segments from transgenic plants failed to initiate hardly any roots. Instead, they continued to form shoots at low frequencies. Moreover, in marked contrast to the controls, stem segments from transgenic plants were able to form shoots even without the addition of exogenous growth regulators to the medium. The results indicate that Spcdc25 expression in culture tobacco stem segments mimicked the developmental effects caused by an exogenous hormone balance shifted towards cytokinins. The observed cytokinin-like effects of Spcdc25 transformation are consistent with the concept of an interaction between cell cycle regulators and phytohormones during plant development.
Keywords: Culture Media; RNA; výhonky rostlin; Cell Cycle Proteins; kyseliny indoloctové; ras-GRF1; genetická transkripce; proteiny buněčného cyklu; tabák; Plant Roots; Indoleacetic Acids; Transcription, Genetic; cytokininy; kořeny rostlin; fungální proteiny; Cytokinins; Plant Shoots; Schizosaccharomyces; Fungal Proteins; kultivační média; Nicotiana